2020
DOI: 10.3390/coatings10121164
|View full text |Cite
|
Sign up to set email alerts
|

Study on Preparation of Superhydrophobic Ni-Co Coating and Corrosion Resistance by Sandblasting–Electrodeposition

Abstract: To enhance the corrosion resistance of type C45E4 substrates, a superhydrophobic Ni-Co coating was prepared on a C45E4 surface by sandblasting pretreatment and electrodeposition. The surface microstructure, three-dimensional surface roughness, and crystal structure of the coating was characterized by scanning electron microscope, laser scanning confocal microscope, and X-ray diffraction. An optical surface contact angle measuring instrument and an electrochemical workstation was used to characterize the wettab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 41 publications
3
5
0
Order By: Relevance
“…From the Figure 4a and the Figure 5a, it can be seen that a large number of random deformations in the form of bulges, flat, and pits were observed on the surface of the grit blasted specimen while the polished surface was flat and smooth with no scratches. Similar result were reported in the previous studies [29,30]. Ni-W coating pretreated by polishing exhibited a less obvious nodular structure on the surface of the morphology which can be attributed to a lower surface roughness of the 45 steel substrates.…”
Section: Surface Morphologysupporting
confidence: 91%
See 1 more Smart Citation
“…From the Figure 4a and the Figure 5a, it can be seen that a large number of random deformations in the form of bulges, flat, and pits were observed on the surface of the grit blasted specimen while the polished surface was flat and smooth with no scratches. Similar result were reported in the previous studies [29,30]. Ni-W coating pretreated by polishing exhibited a less obvious nodular structure on the surface of the morphology which can be attributed to a lower surface roughness of the 45 steel substrates.…”
Section: Surface Morphologysupporting
confidence: 91%
“…Similar results are found by Fu et al and Zhang et al [27,30]. Compared with the base substrate, it was found that the corrosion potential of the Ni-W coating was significantly greater than that of the substrate.…”
Section: Corrosion Resistancesupporting
confidence: 89%
“…The main composition of 45 steel is Fe (elemental iron), and the composition of the remaining minor elements is shown in Table 1. Prior to sandblasting pretreatment for the surface of the 45 steel substrate, a metallographic specimen grinding and polishing machine was used for polishing and #320, #800, and #1500 water sandpaper for mechanical grinding and polishing [23]. Sandblasting pretreatment parameters are shown in Table 2.…”
Section: Preparation Of Workpiece and Coatingsmentioning
confidence: 99%
“…Sandblasting is the most common pretreatment method for metal substrates in the industrial sector. This simple, efficient, and low-cost process uses compressed air to form a high-speed jet beam to spray sand particles at high speed onto the substrate surface to deform it plastically, thereby enhancing the mechanical properties and accelerating the deposition rate of the coating [20][21][22][23][24]. Most studies on electrodeposited composite coatings focused on surface characterization and performance testing such as the influence of microscopic morphology [25,26], grain structure [27,28], and element distribution [29,30] on corrosion resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the lotus effect, a superhydrophobic surface with a water contact angle (CA) more than 150 • and a sliding angle (SA) less than 10 • has attached great interest in both academic research and practical applications owing to its unique properties, involving water-repellency [15][16][17][18], self-cleaning [19][20][21], corrosion resistance [22][23][24][25][26][27][28], antiicing [29,30], oil-water separation [31,32] and drag reduction [33]. Such surface can be realized through the synergistic effect of two main factors: modification with low-surfaceenergy materials and creation of a certain type of hierarchal micro-nanostructure.…”
Section: Introductionmentioning
confidence: 99%